High-Resolution Ex-Vivo Imaging of Retina with a Laptop-Based Portable Endoscope - Yanni Ge; Kai Jin; Yao Wang; Yufeng Xu; Haitong Lu; Juan Ye (Journal of Ophthalmology)
Purpose. Ophthalmic endoscopy is useful in vitreoretinal surgery with opaque anterior segments or anatomically challenging structures. However, standard ophthalmic endoscopy devices are usually large and costly. Thus, the development of a portable endoscope is necessary. Methods. The portable endoscope consisted of a probe, an illumination system, a high-resolution camera module, and a universal serial bus (USB). It was connected to a laptop and applied for intraocular imaging of porcine eyes in vitro. Basic parameters and pictures of the same tissue target were compared with those of the standard Endo Optiks E4 system. Results. The retinal images were displayed on the laptop screen, which clearly showed the overall appearance of the central and peripheral retina, and the details of the retinal vasculature and ciliary body. Compared with a standard endoscope, our portable endoscope is smaller and more affordable. It can be taken anywhere for intraocular imaging and vitreoretinal surgery. Conclusion. A laptop-based portable endoscope is a promising device in vitreoretinal surgery. It provides high-resolution images of intraocular tissues that should make a noticeable difference in intraocular surgery with disordered anterior segments. With its portability and high-resolution imaging, it may promote the application of endoscopes in ophthalmology.